The influence of the rock mineralogy on population density of Chthamalus (Crustacea: Cirripedia) in the Ligurian Sea (NW Mediterranean Sea). Issue 1 (1st January 2019) - Canessa, M.; Bavestrello, G.; Bo, M.; Betti, F.; Gaggero, L.; Cattaneo-Vietti, R.
Abstract: Settlement, recruitment and survival of sessile marine species are driven by many biotic and abiotic factors. Among them, substrate mineral composition is generally a neglected topic, despite it proved to be a relevant contributing variable in driving the structure of benthic communities. Thanks to their ecology, Chthamalus species are a good proxy to test the role of substrate in affecting settlement and final population density on exposed rocky shores. Differences in the number of individuals were analysed in eight localities along the Eastern Ligurian Riviera (north-western Mediterranean Sea), from Portovenere to Manara Cape. In this sector of the Ligurian littoral, the coast is constituted by different rocks characterised by variable concentrations of calcite, silicates and quartz. This situation constitutes an ideal setting to evaluate the influence of mineral composition of the rocks in structuring the epilithic macrobiota communities in energetic splash zones and under similar physical pressures. Rocks rich in calcites turned out to be more suitable for Chthamalus species than substrates containing high amounts of silicates, and of quartz in particular. Additionally, also the grain size of the main mineral component of the rocks, determining in turn the surface roughness seemed to influence barnacle densities, with a significant preference for finer-grained substrates.